2019
DOI: 10.1007/978-3-030-16151-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Teacher Effectiveness Across Time: What Does TIMSS Reveal About Education System Level Trends?

Abstract: To understand whether there are identifiable trends in teacher quality and instructional metrics over time, it is important to first recognize that measures of teacher effectiveness may vary by education system. Descriptive results for the teacher quality measures related to mathematics drawn from twenty years of the IEA's Trends in International Mathematics and Science Study (TIMSS) data provide a general picture of the variation in such measures; additional consideration is given to student-level variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…On the other hand, readiness for TIMSS did not significantly differ when considering teaching experience. This result is consistent with Burroughs et al [32], who showed that a teacher's experience has a role in determining an 8th-grade student's understanding. A more experienced teacher is more likely to use different and friendlier teaching strategies to teach mathematics to students.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…On the other hand, readiness for TIMSS did not significantly differ when considering teaching experience. This result is consistent with Burroughs et al [32], who showed that a teacher's experience has a role in determining an 8th-grade student's understanding. A more experienced teacher is more likely to use different and friendlier teaching strategies to teach mathematics to students.…”
Section: Discussionsupporting
confidence: 92%
“…This is particularly important in those experienced teachers are more likely to use different and effective teaching strategies to teach mathematics to students. Contrary to Burroughs et al [32] and Abdelfattah and Lam [37], Alharbi et al [38] found that students' readiness for mathematics exams is not necessarily affected by their teacher's experience. Others have argued that teaching experience is likely to allow teachers to understand their students better [39] which can aid in the selection of teaching strategies that are congruent with student learning strategies [40].…”
Section: Review Of Related Workmentioning
confidence: 86%
See 2 more Smart Citations